2003
DOI: 10.4269/ajtmh.2003.68.643
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment for Lymphatic Filariasis in Central Nigeria: A Comparison of the Immunochromatographic Card Test and Hydrocele Rates in an Area of High Endemicity

Abstract: The rapid immunochromatographic card test (ICT) for Wuchereria bancrofti circulating filarial antigen is being used to map areas endemic for lymphatic filariasis. However, the ICT is expensive; thus, surveys based on this test must be relatively limited. Our study was conducted to determine if village-based hydrocele surveys could be used to supplement the ICT surveys in the mapping activities. We compared in 144 Nigerian villages the two assessment methods, ICT and examination for clinical hydrocele, in rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
35
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 15 publications
9
35
2
Order By: Relevance
“…Subjects within 73 years and above had no circulating filarial antigen of W. bancrofti in their blood. Eigege et al, (2002) had a similar result in Lafia, Nasarawa State, Nigeria. Also the prevalence of W. bancrofti microfilariae using the Knott's Concentration Techniques shows that subject within the age group 58-62 years had the highest percentage prevalence of 26.09% for male and 18.18% for females.…”
Section: Results Parasitological Findingssupporting
confidence: 66%
See 1 more Smart Citation
“…Subjects within 73 years and above had no circulating filarial antigen of W. bancrofti in their blood. Eigege et al, (2002) had a similar result in Lafia, Nasarawa State, Nigeria. Also the prevalence of W. bancrofti microfilariae using the Knott's Concentration Techniques shows that subject within the age group 58-62 years had the highest percentage prevalence of 26.09% for male and 18.18% for females.…”
Section: Results Parasitological Findingssupporting
confidence: 66%
“…Njenga and Wamae (2001) in Nairobi, Kenya, they established a higher prevalence rate of 37.3% of lymphatic filariasis, using the ICT method, as against 21.13% recorded in this work, using the ICT method also. Eigege et al, (2002) reported a similar prevalence rate of 22.6% using the ICT method in Lafia, Nasarawa State, Nigeria, just as established in this work 21.13% in Afikpo North L.G.A. Ebonyi State.…”
Section: Results Parasitological Findingssupporting
confidence: 61%
“…Although the current report focuses on surveillance to ensure interruption of transmission, morbidity control efforts have also been an essential component of the LF control program in Togo and have recently been described elsewhere. 6,24 Because hydrocele and lymphedema are poor indicators of active filarial burden, 25 they are not currently used for surveillance of LF transmission in Togo; incorporation of these indicators of LF-related morbidity into ongoing surveillance should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…6 Baseline LF mapping using rapid blood antigen detection tests showed mean local government area (LGA) prevalence of 23% (range 4-62%) among persons 15 years of age and older in 70 randomly selected sites in the two states. 7,8 Since 2000, health education plus MDA using 150 μg/kg of ivermectin (Mectizan ; donated by Merck & Co., Inc., Whitehouse Station, NJ) and 400 mg of albendazole (donated by GlaxoSmithKline, Brentford, Middlesex, UK) have been implemented annually according to WHO guidelines to eliminate LF transmission, using each LGA as an independent MDA implementation unit. A phased LGA scale-up to implementing MDA was adopted in the two states as capacity of the program increased and by 2003 all 30 LGAs within the states were under MDA interventions.…”
Section: Introductionmentioning
confidence: 99%